Single-Stage Medial Meniscus Ramp Repair, Lateral Meniscus Root Repair, Revision Anterior Cruciate Ligament Reconstruction and Lateral Extra-Articular Tenodesis - Samundeeswari Saseendar, M.B.B.S., M.S.(Orthop.), M.B.A.; Salim AL. Habsi, M.D.; Ying Ren Mok, M.B.B.S., F.R.C.S.(Ortho.); Yee Han Dave Lee, M.B.B.S., M.M.Ed. (Ortho.), F.R.C.S.(Ortho.), F.A.M.S. (Arthroscopy Techniques)
Revision anterior cruciate ligament reconstruction (ACLR) is being performed increasingly as a result of the growing number of primary ACLR failures. The combined lesions of medial meniscus ramp lesions and lateral meniscus posterior root tears are being observed among many patients who undergo revision ACLR. This combination of meniscus injuries is referred to as ''the new terrible triad.'' Various studies suggest that failing to address these meniscus injuries during primary ACLR can increase the risk of anterior cruciate ligament graft failure. In this technique report, we present our systematic approach to manage medial meniscus ramp lesions and lateral meniscus posterior root tears in revision ACLR.